CENTRAL SENSITIZATION INVENTORY SCORES IN PATIENTS WITH NEUROPATHIC PAIN COMPARED TO HEALTHY SUBJECTS - Popović, Dunja; Ninić, Nemanja; Vojnović, Larisa; Simić Panić, Dušica; Knezevic, Aleksandar (Acta medicae Medianae, 2023)
Central sensitization inventory (CSI) was designed as a tool for evaluation of the symptoms that have been found to be related to central sensitization (CS). The aim of this research was to examine differences in CSI scores between subjects with painful lumbosacral radiculopathy (PLSR). This study included 33 subjects with PLSR (mean age 54.12 ± 9.43 years, 6 (18.2%) women) and 30 healthy subjects (mean age 50.87 ± 5.64 years, 12 (40%) women). The Serbian version of the Central Sensitization Inventory (CSI) was used to examine the degree symptoms related to CS. In order to evaluate the emotional status, we used the Serbian version of the Depression, Anxiety, Stress Scale (DASS 21). The obtained results showed a significantly higher value of the CSI score in subjects with neuropathic pain (t = -7.690, p = 0.000). Statistically significantly worse DASS 21 values in subjects with neuropathic pain in all 3 subscales: depression subscale (t = -2.437, p = 0.018), anxiety subscale (t = -3.597, p = 0.001), stress subscale (t = -3.982, p = 0.000). The degree of expression of symptoms related to CS determined, as well as the degree of anxiety, depression and stress is significantly higher in subjects with PLSR compared to the group of healthy subjects. This should be kept in mind when designing a treatment plan for individuals with PLSR.